Pengaruh Dewan Komisaris, Proporsi Komisaris Independen, Terhadap Kinerja Perusahaan - Brayen Prastika Dwi Putra (Universitas Airlangga, 2015)
The purpose of this study is examined the influence of the composition of the board of commissioners toward the performance of companies from three different aspects; return stock market aspects, ROA aspects of accounting, and accounting aspects and market TobinsQ. This research had a sample of 400 financial records from 400 companies with the period of 2010 to 2013. This research used multiple linear regression method. The independent variable is the number of commissioners and the number of independent commissioners. Moderating variables of this research was the size of the company. The dependent variable was the performance of this company with the company RET measurements, ROA, TobinsQ. The results of this study indicated that for RET, the board had significant negative effect, as well as independent directors had not significant positive effect, while the influence of the board of commissioners of the smaller companies were not exhibited significantly negative. The commissioners had not significant positive effect, independent commissioner had significant positive effect, as well as the board of commissioners had not significant negative effect on the performance of smaller companies to ROA. Research on Tobins Q, the board has a significant positive effect. Independent commissioner also had positive and significant, and the board of commissioners has no significant negative effect on the performance of smaller companies.